Comparative Study of pesticides effects on Artemia salina (Leach, 1819) survival and morphology - Demarco, Mônica (2022)
The use of pesticides has grown over the years and their effects on ecosystems, especially aquatic ones, have been increasingly observed. Agricultural pesticides are responsible for a large part of pollution in aquatic environments, and can reach non-target organisms, harming biodiversity. In this research, the effects of common pesticides on mortality rate and morphology of the model specie Artemia salina were evaluated. Commercial eggs of A. salina were hatched during 24-36 hours, at 37⸰C. Then, nauplli were exposed to different concentrations of insecticides Bifenthrin, Imidacloprid, Diflubenzuron, and Glyphosate herbicide. The mortality rate and lethal concentrations (LC) of each pesticide were established after 24 hours of treatment. Morphological analyses were made after treatment with the LC25 and LC50 of each pesticide. The results obtained show that Bifenthrin, Imidacloprid and Glyphosate promote linear mortality of the non-target species A. salina, while for insecticide Diflubenzuron, the mortality curve followed a logarithmic model. In addition, Diflubenzuron and Glyphosate induce changes in the morphological parameters of this specie. These results contribute to highlight the harmful effects of agricultural pollutants upon aquatic invertebrates. Besides, the present study confirms that Diflubenzuron does not affect only target species, but also has negative interference with the morphology of non-target species. This result has environmental implication since several invertebrates, including those not harmful to agriculture, can contact with Diflubenzuron in agricultural places.